Ancient Greek designs still steal the limelight - Irene Kamberidou (GREECE TODAY, Daily Newspaper, edited in Athens, issue 7, April 5, 1988, section- LIFE STYLE p. 9, 1988)
Irene Kamberidou (1988). Ancient Greek designs still steal the limelight. GREECE TODAY, Daily Newspaper, edited in Athens, issue 7, April 5, 1988, section- LIFE STYLE p. 9.